Global existence of solutions for a class of nonlinear differential equations - Mustafa, OG; Rogovchenko, YV (Pergamon-Elsevier Science Ltd, 2003)
By making use of a special Lyapunov-type function and applying the comparison method due to Conti, we prove global existence of solutions for a general class of nonlinear second-order differential equations that includes, in particular, van der Pol, Rayleigh, and Lienard equations, widely encountered in applications. Relevant examples are discussed. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: global existence; generalized Lienard system; Lyapunov-type function; comparison method